Pengaruh Kampanye Public Relations New Normal terhadap Minat Berkunjung Wisatawan di Heha Sky View Yogyakarta - Kartika Sari Yudaninggar; Inggit Dwi Prabowo (UIN Raden Mas Said Surakarta, 2022)
This study aims to determine whether there is an influence between the public relations campaign adapting to new normal habits at HeHa Sky View Yogyakarta on the interest of visiting tourists. This type of research is quantitative explanatory with data collection techniques through questionnaires and interviews. While the data analysis technique used is the classical assumption test, simple linear regression test, partial test, and the coefficient of determination test. Respondents in this study amounted to 150 respondents. Based on the results of the study, it is known that there is a significant influence between public relations campaigns and tourist interest, especially in the HeHa Sky View tourist attraction. The influence of the public relations campaign on the interest of visiting tourists is 0.324, meaning that the influence of the independent variable on the dependent variable is 32.4%. The public relations campaign has a positive effect on the interest of visiting HeHa Sky View tourists with a regression coefficient of 0.758. This means that for every 1% addition to the value of the public relations campaign, the value of the interest in visiting tourists increases by 0.758.